Performance Study of Wireless Access in Vehicular Environment 802.11p in Ad-Hoc on Demand Distance Vector Routing (AODV) with Propagation Models Nakagami and Two Ray Ground - Erna Auparay; Radityo Anggoro; Royyana M. Ijtihadie (Institut Teknologi Sepuluh Nopember, 2018)
The development of communication systems is not only limited in its use for human interaction and mobility with various electronic devices. However, it is expected to be a solution for traffic management and management strategies. The number of vehicles is continuously increasing especially in big cities so it needs communication between vehicles for the development of VANETs technology. The IEEE international standards communication system establishes the use of the Wireless Access in Vehicular Environment (WAVE). With the IEEE 802.11p standard, it is possible to build an integrated information and communication-based transportation system.In this research will be analyzed VANET communication performance through parameters of packet delivery ratio, routing overhead, and packet drop. VANET uses NS-2 as a simulator and AODV routing protocol. In a network, routing protocols are very influential on VANET network performance. Simulation scenarios with VANET using Nakagami and TwoRayGround propagation models are expected to result in connectivity performance on interoperable communication networks (V2V) with IEEE 802.11p standards in VANET environments. From the experimental results in the AODV protocol scenario using propagation modeling, the value of packet delivery ratio, routing overhead, and packet drop with the Nakagami transmission model is better than the value of packet delivery ratio, routing overhead, and packet drop with TwoRayGround transmission model has good value but Unstable in the node transmission process. Thus, the performance of the Nakagami transmission model looks more stable overall than the TwoRayGround transmission mode